Teacher‐ Versus Video‐Delivered Classroom Activity Breaks and Student Physical Activity: The PAAC ‐3 Trial - Amanda N. Szabo‐Reed; Richard A. Washburn; Jaehoon Lee; Anna Gorczyca; Jeffery J. Honas; Joseph E. Donnelly (Journal of School Health, 2026)
ABSTRACT Background Classroom activity breaks may increase moderate‐to‐vigorous physical activity (MVPA); however, few studies have compared teacher and video‐delivered approaches under real‐world conditions. Methods In this cluster randomized trial, 11 elementary schools were assigned to teacher‐delivered (PAAC‐T; 5 schools, 192 students) or video‐delivered (PAAC‐V; 6 schools, 276 students) classroom activity breaks across one academic year. Teachers were trained to deliver two 10‐min breaks daily. Intervention delivery was tracked via a web‐based platform, and classroom MVPA was assessed using accelerometers at baseline and follow‐up. Results Implementation fidelity was low and highly variable, but comparable between PAAC‐T (42.3 ± 57.1 activity breaks/teacher/year) and PAAC‐V (39.2 ± 33.9; p = 0.96), with teachers delivering ∼50% of the intended daily activity. Classroom MVPA increased significantly in both groups (PAAC‐T: 9.8 ± 15.9; PAAC‐V: 9.1 ± 15.3 min/day; p < 0.001), with no intervention arm‐by‐time interaction ( p = 0.43). Implications for School Health Policy, Practice, and Equity Classroom physical activity breaks may increase student MVPA, but effectiveness in elementary schools appears to depend on implementation fidelity, administrative support, and equitable system‐level infrastructure. Conclusions Modest increases in classroom MVPA were observed across both delivery formats, although low and variable implementation fidelity limited conclusions regarding effectiveness and highlighted the need for stronger implementation supports. Trial Registration: NCT03493139.